Modeling the TTL at Continental Scale for a Wet Season: An Evaluation of the BRAMS Mesoscale Model Using TRO-Pico Campaign, and Measurements From Airborne and Spaceborne Sensors - Behera, Abhinna K.; Riviere, Emmanuel D.; Marecal, Virginie; Rysman, Jean-Francois; Claud, Chantal; Seze, Genevieve; Amarouche, Nadir; Ghysels, Melanie; Khaykin, Sergey M.; Pommereau, Jean-Pierre; Held, Gerhard [UNESP]; Burgalat, Jeremie; et al. (Amer Geophysical Union, 2018)
In order to better understand the water vapor (WV) intrusion into the tropical stratosphere, a mesoscale simulation of the tropical tropopause layer using the BRAMS (Brazilian version of Regional Atmospheric Modeling System (RAMS)) model is evaluated for a wet season. This simulation with a horizontal grid point resolution of 20kmx20km cannot resolve the stratospheric overshooting convection (SOC). Its ability to reproduce other key parameters playing a role in the stratospheric WV abundance is investigated using the balloon-borne TRO-Pico campaign measurements, the upper-air soundings over Brazil, and the satellite observations by Aura Microwave Limb Sounder, Microwave Humidity Sounder, and Geostationary Operational Environmental Satellite 12. The BRAMS exhibits a good ability in simulating temperature, cold-point, WV variability around the tropopause. However, the simulation is typically observed to be warmer by approximate to 2.0 degrees C and wetter by approximate to 0.4 ppmv at the hygropause, which can be partly affiliated with the grid boundary nudging of the model by European Centre for Medium-Range Weather Forecasts operational analyses. The modeled cloud tops show a good correlation (maximum cross-correlation of approximate to 0.7) with Geostationary Operational Environmental Satellite 12. Furthermore, the overshooting cells detected by Microwave Humidity Sounder are observed at the locations, where 75% of the modeled cloud tops are higher than 11km. Finally, the modeled inertia-gravity wave periodicity and wavelength are comparable with those deduced from the radio sounding measurements during TRO-Pico campaign. The good behavior of BRAMS confirms the SOC contribution in the WV abundance, and variability is of lesser importance than the large-scale processes. This simulation can be used as a reference run for upscaling the impact of SOC at a continental scale for future studies.